Millennials as Religious Tolerance Agents - Roma Wijaya (Publication of the International Journal and Academic Research, 2024)
The 21st century is known to the public as the millennium era or the millennial generation. People who fall into this group are those born around the 1980s and 1990s, even up to the 2000s. The dynamics of social change experienced by the millennial dynasty is that it is routinely dominated by technology, especially the internet and smartphones. Millennials' morals and behavior experience abstract patterns, because they imitate from the internet, especially social media ranging from Facebook, Instagram, YouTube, TikTok, and others. Supposedly, the triumph of technology today is a tool to realize religious tolerance. However, until now the phenomenon of intolerance is still rolling like a ball that is always contested. This article aims to explore the social dynamics of millennial groups who become agents of implementing religious tolerance values. This paper uses a descriptive-analytic approach. The result is Millennials who are considered proficient in internet technology based on social media utilize it to access and disseminate to the public content with tolerance nuances. In addition to accessing accounts or websites based on tolerance values such as UNOY, YIPC, Peace Generation, and so on. Millennials can also create personal accounts or websites with cultural, racial, political, and religious diversity content. Instead of accessing or spreading hateful posts to each other.